Application and prospects of near-infrared fluorescence guided surgery in the treatment of oral cancer - XIE Diya; XIAO Tao; SHAN Danni; ZHOU Ting; WANG Zhiyong (Kouqiang hemian waike zazhi)
The complete resection of tumor and metastatic cervical lymph nodes are the key to the successful surgical treatment of oral cancer. However, during the operation, surgeons do not have a convenient and effective auxiliary means to evaluate the completeness of tumor eradication, in addition to relying on frozen biopsy techniques. In recent years, with the development of near-infrared fluorescence (NIF) imaging, fluorescence-guided surgery (FGS) has gradually evolved, providing important real-time intraoperative assistance for surgeons, and has also been widely recognized and applied in clinical practice. The application of fluorescence imaging in the surgical treatment of oral squamous cell carcinoma (OSCC) is still in its early stages. This article introduces the specific clinical application scenarios of this technology in oral cancer surgery, discusses the current challenges, and looks forward to future development, so as to provide reference for its clinical application and research.